Transcutaneous bilirubinometry in preterm infants: A literature review - Wahyuni, Rita (Holistik Jurnal Kesehatan, 2024)
Background: Hyperbilirubinemia is a problem that often occurs in premature babies. Measuring the correct bilirubin levels from the start will reduce the risk of complications of hyperbilirubinemia. Transcutaneous bilirubin (TcB) is a measurement that is still accurate today in screening for jaundice in premature babies.Purpose: To provide an overview of measuring TcB (Transcutaneous Bilirubin) in premature babies.Method: Literature review research by searching for academic articles through online databases, searching through online databases including Science Direct, Scopus, ProQuest, and Google Scholar from 2013-2023 and obtained 10 suitable articles.Results: In a review of selected journals, it was found that TcB measurements are still recommended in screening for hyperbilirubinemia or jaundice, especially in premature babies. TcB also has results close to TSB in cases of premature babies receiving phototherapy and after phototherapy. Taking TcB from the forehead or sternum area is still an alternative option when taking measurements. TcB reduces the percentage of invasive procedures for taking TSB (Total Serum Bilirubin) in babies. However, consuming TSB also pays attention to medical indications.Conclusion: The use of TcB as a screen for hyperbilirubinemia in premature babies is a non-invasive treatment option for treating premature babies. TcB results are still accurate compared to TSB results. However, you still have to be careful, especially in premature babies <33 weeks and after the baby has received phototherapy. Keywords: Neonatal Jaundice; Preterm Infants; Transcutaneous Bilirubin.Pendahuluan: Hyperbilirubinemia adalah masalah yang kerap terjadi pada bayi prematur. Pengukuran kadar bilirubin yang tepat sedari awal akan mengurangi resiko komplikasi hyperbilirubinemia. Transkutaneous bilirubin (TcB) adalah pengukuran yang masih akurat sampai sekarang dalam skrining jaundice pada bayi prematur.Tujuan: Untuk memberi suatu gambaran mengenai pengukuran TcB (Transkutaneous Bilirubin) pada bayi prematur. Metode: Penelitian literature review dengan penelusuran artikel akademik melalui online database antara lain Science Direct, Scopus, ProQuest, dan Google Scholar dari tahun 2013-2023 dan didapatkan 10 artikel yang sesuai.Hasil: Dalam telaah review jurnal yang dipilih, didapatkan pengukuran TcB masih direkomendasikan dalam skrining hyperbilirubinemia atau jaundice, terutama pada bayi prematur. TcB juga mempunyai hasil yang mendekati TSB pada kasus bayi prematur yang mendapat fototerapi dan sesudah fototerapi. Pengambilan TcB pada daerah dahi atau tulang dada masih menjadi alternatif pilihan saat pengukuran. TcB mengurangi persentase tindakan invasif pengambilan TSB (Total Serum Bilirubin) pada bayi. Akan tetapi pengambilan TSB juga dipertimbangkan sesuai indikasi medis. Simpulan: Penggunaan TcB sebagai skrining hyperbilirubinemia pada bayi prematur merupakan pilihan tindakan non invasif pada perawatan bayi prematur. Hasil TcB masih akurat dibandingkan dengan hasil TSB. Akan tetapi tetap harus hati-hati terutama pada bayi prematur usia kehamilan <33 minggu dan setelah bayi mendapat tindakan foto terapi. Kata Kunci: Neonatal Jaundice; Preterm Infants; Transcutaneous Bilirubin.